Complex bandpass filtering for coriolis mass flow meter signal processing - Li, M; Henry, M (IEEE, 2016)
This paper explores the possible application of the complex bandpass filter in Coriolis mass flow meter signal processing. The method shows high robustness for frequency, amplitude and phase tracking under noisy conditions, such as those generated by two-phase (gas/liquid) flow. Simulations of the new technique are compared with existing academic and industrial signal processing solutions to evaluate their relative performance.